PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 013 LUBUK KEMBANG SARI KECAMATAN UKUI - Arleni Tarigan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve student learning outcomes in social studies on the subject matter of buying and selling activities in the home and school environment through the application of the role-playing learning model in third-grade students of SD Negeri 013 Lubuk Kembang Sari, Kecamatan Ukui. The low learning outcomes of grade III students were caused by the teacher not applying an appropriate learning model, resulting in students having difficulty understanding the material. The subjects of this study were 18 third-grade students consisting of 12 male and 6 female students. The parameters measured included teacher activities, student activities, and student learning outcomes, analyzed descriptively. The results showed an increase in teacher activity from 75% at the first meeting of cycle I (good), 77.8% at the second meeting of cycle I (good), 86.1% at the first meeting of cycle II (very good), and 88.9% at the second meeting of cycle II (very good). Student activity also increased from 61.1% at the first meeting of cycle I (good), 77.8% at the second meeting of cycle I (good), 80.6% at the first meeting of cycle II (very good), and 86.1% at the second meeting of cycle II (very good). Classical completeness of learning outcomes increased from 39.5% at the baseline (not complete) to 81.6% in the first daily test (complete) and 92.1% in the second daily test (complete). Based on these results, it is concluded that the application of the role-playing learning model can improve student learning outcomes in social studies.